Physical Diagnosis and Rehabilitation Technologies - Liu, Tao; Ferreira, João (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book focuses on the diagnosis, evaluation, and assistance of gait disorders; all the papers have been contributed by research groups related to assistive robotics, instrumentations, and augmentative devices.